Crystallographic Preferred Orientation of Olivine in Sheared Partially Molten Rocks: The Source of the "a‐c Switch". (2nd February 2018) - Qi, Chao; Hansen, Lars N.; Wallis, David; Holtzman, Benjamin K.; Kohlstedt, David L.
Abstract: To investigate the mechanism that produces the crystallographic preferred orientations (CPO) characteristic of sheared partially molten rocks of mantle composition, we analyzed the microstructures of samples of olivine plus 7% basaltic melt deformed in torsion to shear strains as large as γ = 13.3. Electron backscattered diffraction (EBSD) observations reveal a CPO characterized by a weak a‐c girdle in the shear plane that develops by γ ≈ 4. This CPO, which exhibits a slightly stronger alignment of [001] than [100] axes in the shear direction, changes little in both strength and distribution with increasing stress and with increasing strain. Furthermore, it is significantly weaker than the CPO observed for dry, melt‐free olivine aggregates. Orientation maps correlated with grain shape measurements from tangential, radial, and transverse sections indicate that olivine grains are longer along [001] axes than along [100] axes and shortest along [010] axes. This morphology is similar to that of olivine grains in a mafic melt. We conclude that the weak a‐c girdle observed in sheared partially molten rocks reflects contributions from two processes. Due to their shape‐preferred orientation (SPO), grains rotate to align their [001] axes parallel to the flow direction. At the same time, dislocation glide on the (010)[100] slip system rotates [100] axes into the flow direction. The presence of this CPO in partially molten regions of the upper mantle significantly impacts the interpretation of seismic anisotropy and kinematics of flow. Key Points: A CPO of olivine with girdles of [100] and [001] axes in the shear plane occurs in sheared partially molten mantle rocks This observed CPO is weak, exhibits little change with strain and stress, and induces different seismic anisotropy from melt‐free olivine We proposed a model consisting of two mechanisms for CPO formation to explain the occurrence and evolution of the observed CPO